The photometrical system and positional accuracy of the CCD camera ST7 of Lisnyki Observational Station - Kleshchonok, V.V.; Pogoreltsev, M.T.; Andruk, V.M.; Lukyanyk, I.V. (Кинематика и физика небесных тел, 2005)
The results of testing of CCD ST7 camera are reported. Determinations of photometrical system and positional accuracy were made by processing of open cluster Stock 1 observations at the AZT-8 telescope of the Lisnyki Observational Station.